2019
DOI: 10.3390/dj7040099
|View full text |Cite
|
Sign up to set email alerts
|

Q-Switch Nd:YAG Laser-Assisted Decontamination of Implant Surface

Abstract: Peri-implantitis (PI) is an inflammatory disease of peri-implant tissues, it represents the most frequent complication of dental implants. Evidence revealed that microorganisms play the chief role in causing PI. The purpose of our study is to evaluate the cleaning of contaminated dental implant surfaces by means of the Q-switch Nd:YAG (Neodymium-doped Yttrium Aluminum Garnet) laser and an increase in temperature at lased implant surfaces during the cleaning process. Seventy-eight implants (titanium grade 4) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 42 publications
5
38
0
Order By: Relevance
“…Regarding the comparison of our findings with the current evidence found in the literature, a previous study of Namour et al [21] demonstrated that similar laser irradiation conditions to those used in our study using the Q-Switch Nd: YAG laser led to a total detachment of all organic and non-organic (calculus) elements, and therefore, a total elimination of calculus, organic, debris, germs, toxins, and any carbonic element. Another recent study by Namour et al [22] showed that irradiation conditions similar to the conditions used in our study can lead to the total elimination of multi-species biofilm from irradiated titanium surfaces [22].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Regarding the comparison of our findings with the current evidence found in the literature, a previous study of Namour et al [21] demonstrated that similar laser irradiation conditions to those used in our study using the Q-Switch Nd: YAG laser led to a total detachment of all organic and non-organic (calculus) elements, and therefore, a total elimination of calculus, organic, debris, germs, toxins, and any carbonic element. Another recent study by Namour et al [22] showed that irradiation conditions similar to the conditions used in our study can lead to the total elimination of multi-species biofilm from irradiated titanium surfaces [22].…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the comparison of our findings with the current evidence found in the literature, a previous study of Namour et al [21] demonstrated that similar laser irradiation conditions to those used in our study using the Q-Switch Nd: YAG laser led to a total The null hypothesis was rejected because there is a significant difference between the level of disinfection of contaminated and untreated titanium surfaces (Group C) and those that have been contaminated and laser-treated (Group L) having total surface disinfection.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Apart from wavelength, tissue response is affected by power, energy density and radiation dose. An increase in power and energy density leads to intensification of thermal and ablative processes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%